Linguistics in the courtroom : a practical guide - Shuy, Roger W. (Oxford University Press, 2006)
Useful for both beginning and established linguists, this book deals with issues of how linguists first become and then represent themselves as experts. It also talks about how they can manage the practice of consulting on law cases, how they can address important issues of professional ethics, and how they can work most effectively with lawyers.